EFFECTIVENESS OF ERGONOMIC EXERCISE ON BLOOD SUGAR IN DIABETES MELLITUS PATIENTS - Wahyuni, Lutfi; Kusumaningrum, Umi Azizah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Diabetes is a chronic metabolic disorder characterized by hyperglycemia because the pancreas is unable to produce enough insulin and the body is unable to use insulin effectively. If diabetes mellitus is not treated properly, it will cause acute and chronic complications. Physical activity training is one of the non-pharmacological management of diabetes mellitus. One form of physical activity training is ergonomic gymnastics. This study aims to determine the effect of ergonomic exercises on blood sugar levels in patients with diabetes mellitus in Krembung Public Health Center. This research is a quantitative study using Pre-Experimental Design One Group Pre- Test Post-Test with 36 respondents. This study shows that there is a decrease in the average blood sugar level on the first day of 234 mg/dL to 209.5 mg/dL, on the second day the average blood sugar level from 211.5 mg/dL to 187.7 mg/dL while the average blood sugar level of the third meeting from 175.7 mg/dL to 148.8 mg/dL. Ergonomic gymnastics involves the main muscles that can make insulin receptors increase and more sensitive so as to reduce blood sugar levels. This is evidenced by the results of the analysis using the Paired T-Test test obtained a p-value of 0.000 (<0.05) which shows the effect of ergonomic exercises on blood sugar levels in patients with diabetes mellitus in Krembung Public Health Center. Based on the results of this study, ergonomic exercises are important to be done routinely in patients with diabetes mellitus to reduce blood sugar levels.